Vertical Displacement of the Equine Pelvis When Trotting on an Aqua Treadmill. (June 2014) - York, J; Walker, A
Abstract : Introduction: Hydrotherapy is increasingly applied within the equine industry for rehabilitation and therapy. Substantial anecdotal evidence exists suggesting the benefits of its application but while there is extensive literature on the use of aqua‐treadmills in humans and canines there is comparatively little in equines. Therefore, limited research exists supporting the role of the aqua‐treadmill in current therapy practices. This study aimed to investigate the effect of water depth on pelvic movement during aqua‐treadmill exercise. Methods: Eight horses were trotted on an aqua‐treadmill at four water depths specifically measured to individual horses (P3, fetlock, MC3, carpus). Pelvic displacement was recorded using an optical motion capture system to collect coordinates from markers placed on the tuber sacrale, tuber coxae, withers and lumbar spine. Data were processed using custom written scripts (Matlab®) and ANOVA was performed. Results: All subjects demonstrated a significant increase in vertical displacement of the pelvis as water depth increased from P3 to carpus while displacement symmetry was not significantly altered with a change in water depth. Conclusions: The common practice of increasing water depth to intensify the physical demands of the exercise while maintaining the desired movement symmetry is supported. Having knowledge of how a horse moves on an aqua‐treadmill is vital for tailoring specific therapy in order to most successfully rehabilitate the horse from injury. Investigation of the effects of increasing water depth on asymmetric horses should be carried out to further support its application as a tool for rehabilitation. Ethical Animal Research: Ethical approval was obtained from the Ethics Review Committee at Moulton College. Owner consent was granted for all subjects and all horses were handled in compliance with British Horse Society standards throughout the trials.Sources of funding: Thomas Harrison Trust at Moulton College.Competing interests: none.